Metodologi Al-Fiqh Al-Muqāran: Pendekatan dan Dampaknya Pada Perbedaan Pendapat Fiqh - Wipkil Bashor; Muhammad Furqon Almurni; Sofyan Al-Hakim; Jajang Komaludin; Jajat Sudrajat (STAI Al-Mas'udiyah, 2025)
This research focuses on exploring the methods used by scholars in studying comparative fiqh (al-Fiqh al-Muqāran), the reasons behind differing opinions among them, and the benefits that can be gained from studying comparative fiqh. Utilizing a literature study approach and descriptive analysis, this research reveals that: (1) The process of comparative fiqh is conducted through comparison and critique of contradictory opinions to achieve scientific clarity, which includes weighing, identifying similarities and differences, investigating the reasons for differences, and finding solutions through compromise or selecting the more argumentatively strong opinion. (2) Factors causing differences in opinion among jurists include differences in qirā’ah (recitations), irāb (grammatical inflection), ḥadīth narrations, text interpretation, sources of legal deduction (istinbāṯ), and methods of integrating and prioritizing contradictory evidence. (3) The benefits of studying al Fiqh al Muqāran include understanding the basic principles of fiqh schools, the ijtihad approach of the jurists, their method of legal reasoning (istinbāt), and their critique of evidence. Additionally, this study aids in developing fiqh skills, expanding the understanding of ijtihad and its flexibility, understanding the ethics of scholars in dealing with differing opinions to reach the truth, and appreciating the strong foundations behind these differences. This research offers significant insights into the importance of comparative fiqh in enriching Islamic understanding, valuing diversity of opinion, and promoting an attitude of tolerance and respect in the discourse of Islamic scholarship.